Influence of ambidexterity on SME export performance: Analysis of the mediating effect of strategic flexibility in Turkey - Brulhart, Franck; Vieu, Marion; Unal, Nesibe; Métailler, Thibaut (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2025)
In this paper we address the theme of the influence of ambidexterity and strategic flexibility on the export performance of SMEs in the context of emerging markets. Surveying a sample of 305 exporting Turkish SMEs, we test specific hypotheses concerning the respective roles of ambidexterity and strategic flexibility in directly affecting the export performance of the SME. We also test the mediating role of strategic flexibility in the relationship between ambidexterity and export performance. Our results show that ambidexterity has no direct influence on export performance. They further show that coordination flexibility and decision-making flexibility mediate the relationship between ambidexterity and export performance.